ASSESSMENT OF INVESTMENT ACTIVITY MANAGEMENT AT TEXTILE INDUSTRY ENTERPRISES IN THE REPUBLIC OF UZBEKISTAN - Guzal Umarova (Scholar Express Journals, 2024)
The textile industry is one of the key sectors of the economy of Uzbekistan. The implementation of environmentally friendly production technologies, the observance of working conditions, the use of sustainable materials and the recycling of waste products contribute to the economic growth of the country, the reduction of negative impact on the environment and improvement of the living conditions of the population. In the context of deepening integration processes in the world, many scientific studies are being conducted on investment management in the strategic development of textile enterprises. The purpose of the article is to develop scientific, methodological and practical proposals for attracting investment in enterprises, which operate as the part of the Association “Uztekstilprom” and organize their effective management. The article proposes a method for assessing the effectiveness of investment management in the strategic development of a textile enterprise. The method has been improved thanks to the use of limits on the integral indicator of investment management efficiency (rating assessment). The approach to ensuring the compatibility of the goals of generating income or increasing the value of assets that determine the investment policy, when assessing the effectiveness of investment management in the strategic development of a textile enterprise, with the level of activity in managing the investment portfolio and types of assets is substantiated. The proposed internal control mechanism is aimed at increasing the efficiency of investment management at textile enterprises by ensuring the effective structuring of investment activity processes, as well as the harmony of direct interest in its results based on assessing the personal participation of managers at various levels in accordance with their performance capabilities and skill level. The developed methodological proposals, scientifically based recommendations and conclusions can be used to ensure the volume expansion of theoretical and practical knowledge regarding the system, tools and mechanisms of investment management in the textile industry.
Keywords: investment; regions; export potential